2016
DOI: 10.1159/000453166
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells with Enhanced Bcl-2 Expression Promote Liver Recovery in a Rat Model of Hepatic Cirrhosis

Abstract: Background/Aims: Mesenchymal stem cell (MSC) transplantation has emerged as an option for the treatment of chronic hepatic cirrhosis, while its therapeutic efficacy could be improved. The bcl-2 gene is anti-apoptotic and can help cell survival and proliferation. Therefore, we explored whether transplanted MSCs with enhanced bcl-2 expression may be beneficial in the treatment of experimental cirrhosis in rats. Methods: MSCs were isolated from rat bone marrow, expanded in vitro and transfected with adeno-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…On the other hand, apoptosis plays an important role in cell proliferation, differentiation, senescence and death. The potential to induce HSC apoptosis has also become an important strategy in the treatment of liver fibrosis [25, 26]. In the present study, our results firstly showed that trolline markedly promoted HSC-T6 cell apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, apoptosis plays an important role in cell proliferation, differentiation, senescence and death. The potential to induce HSC apoptosis has also become an important strategy in the treatment of liver fibrosis [25, 26]. In the present study, our results firstly showed that trolline markedly promoted HSC-T6 cell apoptosis.…”
Section: Discussionsupporting
confidence: 59%
“…Carbon tetrachloride (CCl 4 ) is a well-known hepatotoxin that is widely used to induce experimental liver fibrosis and cirrhosis in rodents [5]. CCl 4 -induced hepatotoxicity is believed to involve two phases.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used rat liver progenitor cell WB-F344 as LPC cell model and HGF as inducer to simulate the process of LPCs hepatic differentiation [29]. Moreover, the hepatocyte cell trait was characterized in terms of hepatocellular function, hepatocellular morphology, and hepatocyte-specific markers [30].…”
Section: Discussionmentioning
confidence: 99%